2017
DOI: 10.2214/ajr.16.16851
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Susceptibility Variation of Normal-Appearing White Matter in Multiple Sclerosis by Quantitative Susceptibility Mapping

Abstract: In patients with RRMS and gadolinium-nonenhancing lesions, the susceptibility values of NAWM decrease when gadolinium-enhancing lesions appear, approaching values similar to those of WM in healthy control subjects, suggesting that NAWM may contribute to the iron accumulation observed in early active MS lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…A recent study reported increased NAWM QS in patients who had only non-enhancing lesions compared to HC subjects, and no significant difference in patients with enhancing lesions [44]. However, among patients in our study with only non-enhancing lesions, we found no significant QS difference between whole-brain NAWM compared to HCWM.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…A recent study reported increased NAWM QS in patients who had only non-enhancing lesions compared to HC subjects, and no significant difference in patients with enhancing lesions [44]. However, among patients in our study with only non-enhancing lesions, we found no significant QS difference between whole-brain NAWM compared to HCWM.…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, iron content in NAWM may vary between different patients (i.e., relapsing–remitting versus primary progressive subtypes) as well as within the same patient over time [44]. With regard to the latter, Hametner et al found iron deposition in the NAWM of patients with acute MS similar to healthy populations, while patients with chronic disease exhibited iron depletion [38].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative susceptibility mapping (QSM) enables the quantitative measurement of tissue magnetic susceptibility, which is a measure of how tissue responds to an external magnetic field . QSM has been used increasingly in clinical brain studies, particularly for visualizing and quantifying iron in brain diseases, including multiple sclerosis (MS), distinguishing calcifications and hemorrhage, and preoperative planning for deep brain stimulation . In the brain, QSM technology has advanced to a stage of high reproducibility as demonstrated by various groups .…”
Section: Introductionmentioning
confidence: 99%
“…CNS abnormalities beyond obvious MS plaques are also well documented . The “normal‐appearing white matter” (NAWM) is a commonly described feature of white matter that appears normal on conventional MRI, but abnormalities can be detected using advanced MRI …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The "normal-appearing white matter" (NAWM) is a commonly described feature of white matter that appears normal on conventional MRI, but abnormalities can be detected using advanced MRI. [9][10][11][12][13][14][15][16][17] A less often reported, but still common, feature in MS is regions of white matter with signal intensity intermediate between NAWM and MS lesions on T 2 and proton density imaging, termed diffusely abnormal white matter (DAWM) 18,19 (Fig 1), formerly termed "dirty-appearing white matter." By definition, DAWM is diffuse with ill-defined borders and has signal intensity similar to gray matter on proton density and T 2 scans, but is found in white matter locations.…”
Section: Introductionmentioning
confidence: 99%